MANAJEMEN PRODUKSI PENGOLAHAN IKAN BANDENG DI KABUPATEN PATI UNTUK PENGEMBANGAN PRODUK EKSPOR - Sugito -; Alan Prahutama; Abdul Hoyyi (Universitas Muhammadiyah Semarang, 2017)
Central Java as one of the regions in Indonesia which has various food preparations. One typical souvenirs Semarang, which is the capital of Central Java province is milkfish presto, milkfish brains, chips and shredded milkfish milkfish. Aquaculture fish of the largest in Central Java is located in Pati regency. One of the famous places that serve as souvenirs of milkfish is Juwana area, Pati. Many SMEs (Small and Medium Enterprises) in Pati engaged in the processing of aquaculture fish, one of which is milkfish presto. In this paper, the researchers took two of SMEs as a form of field studies engaged in the processing of fish. SMEs are SMEs milkfish Presto twin source of fortune and SMEs banding without thorns excellent. Both of us empower SMEs for the development of export products. In the first year field study outcome shows that the manufacture of standard operating procedures (SOP) and product diversification is the first step the product criteria ekspor. Also marketing techniques is an important factor in the expansion of the market.Keywords: Processed milkfish; Diversification of products; marketing Management; SOP; SME in Pati.